GovTech for Armenia : A Whole of Government Approach as a Key Foundation for the Digital Economy in Armenia - World Bank (World Bank, Washington, DC, 2021)
This note presents main findings of the GovTech snapshot assessment for Armenia forming part of a larger World Bank global engagement on GovTech and Advisory Services and Analytics (ASA) in the South Caucasus on transforming government services through digital innovations. The objective of the note is to conduct an initial GovTech stock-taking using the GovTech conceptual framework within the broader digital economy context. Starting with a first analytic phase in 2021 and to be continued through a second phase of implementation support in 2022, the assessment focuses on key thematic areas in line with client’s interest to help identify entry-points and reform options. It applies a simplified and customized version of the Digital Government Readiness Assessment Methodology (DGRA), assessing key thematic dimensions and developing a menu of reform options in line with client priorities. The note is structured in four sections. The first section presents the GovTech and Digital Economy conceptual framework. Section two includes key findings of the snapshot assessment for all nine dimensions of the DGRA. Section three propose potential reform opportunities based on entry-points identified in the assessment and customized to client priorities. These are presented below as a preliminary menu of reform options and as a basis for further discussion with Armenian counterparts. Finally, Section 4 presents different GovTech engagement options to deepen collaboration between the government of Armenia and the World Bank.